Pola Komunikasi Forum Kerukunan Antarumat Beragama (FKUB) Dalam Menciptakan Kerukunan Antarumat Beragama di Kota Medan - DIta Khairiza; Muhammad Husni Ritonga (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Effective communication patterns are the key to creatng harmony between varous religions in the city of Medan. The Diversity Harmony Forum (FKUB) is an institution that plays an important role in promoting dialogue, understanding, and cooperation between various religions and beliefs iin the city of Medan. Ths study ams to analyze the communication patterns used by FKUB in creating harmony between various faths in the city of Medan. The research method used is qualitative research by condiucting in-diepth interviews with FKUB members and studying documentation related to FKUB activties. The results of the study show that FKUB's communication patterns are based on the principles of mutual respect, listening wth empathy, andi seeking solutions together. In iinternal communication, FKUB uses regular meetings and discusson groups to strengthen understanding and togetherness among members. Meanwhle, in external communication, FKUB implemented various strategies such as interfaith dialogue, join social activities, andi public campaigns to encourage dialogue between diverse people in Medan City. Keywordis: communication pattern, forum for harmony among various people, harmony between various religions, Medan City.